2022
DOI: 10.3389/ijph.2022.1604608
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Study on Maternal Depressive Symptoms During the COVID-19 Pandemic: The Role of Strict Lockdown Measures and Social Support

Abstract: Objectives: This study examined the trajectory of perinatal depressive symptoms in Portuguese women during the COVID-19 pandemic and the role of individual, relational, and contextual risk and protective factors.Methods: This 3-wave longitudinal study followed 290 pregnant women from the third trimester of pregnancy until 6-months postpartum. Women self-reported on depressive symptoms, psychological (anxiety, perceived stress, mindfulness), relational (perceived social support, dyadic adjustment, sexual wellbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 47 publications
3
2
0
Order By: Relevance
“…Findings indicate that greater negative COVID impact, lower education, and lower social support were positively associated with higher levels of distress levels during pregnancy. These findings are in line with prior research indicating that social support is a protective factor (e.g., Lebel et al, 2020;Zhou et al, 2021;Khoury et al, 2021b;Fernandes et al, 2022) and COVID-related stress is a risk factor (e.g., Khoury et al, 2021b;Awad-Sirhan et al, 2022;Giesbrecht et al, 2022) for mental health and distress in prenatal and postpartum samples during the pandemic. In particular, prior work by Fernandes et al (2022) showed that higher social support was associated with lower levels of depression from pregnancy 6-months postpartum.…”
Section: Factors Related To Distress: Education Level Covid Impact An...supporting
confidence: 91%
See 2 more Smart Citations
“…Findings indicate that greater negative COVID impact, lower education, and lower social support were positively associated with higher levels of distress levels during pregnancy. These findings are in line with prior research indicating that social support is a protective factor (e.g., Lebel et al, 2020;Zhou et al, 2021;Khoury et al, 2021b;Fernandes et al, 2022) and COVID-related stress is a risk factor (e.g., Khoury et al, 2021b;Awad-Sirhan et al, 2022;Giesbrecht et al, 2022) for mental health and distress in prenatal and postpartum samples during the pandemic. In particular, prior work by Fernandes et al (2022) showed that higher social support was associated with lower levels of depression from pregnancy 6-months postpartum.…”
Section: Factors Related To Distress: Education Level Covid Impact An...supporting
confidence: 91%
“…These findings are in line with prior research indicating that social support is a protective factor (e.g., Lebel et al, 2020;Zhou et al, 2021;Khoury et al, 2021b;Fernandes et al, 2022) and COVID-related stress is a risk factor (e.g., Khoury et al, 2021b;Awad-Sirhan et al, 2022;Giesbrecht et al, 2022) for mental health and distress in prenatal and postpartum samples during the pandemic. In particular, prior work by Fernandes et al (2022) showed that higher social support was associated with lower levels of depression from pregnancy 6-months postpartum. The present study adds to this literature by demonstrating longitudinal effects of social support and COVID stress on trajectories of multiple indices of distress (depression, anxiety, and stress) from pregnancy to 15-months postpartum.…”
Section: Factors Related To Distress: Education Level Covid Impact An...supporting
confidence: 91%
See 1 more Smart Citation
“…Our ndings demonstrated that the negative between PSS and for women in low, moderate and high pandemic severity. Similar ndings reinforced that PSS had a strong protective effect against depressive symptoms when women were under severe lockdown strictions during COVID-19 [43].…”
Section: Associations Of Pss and Pds Under Different Covid-19 Pandemi...supporting
confidence: 69%
“…Recruitment occurred either in‐person at regularly scheduled clinical appointments to gynecologists in an obstetrics outpatient unit (81%) or via community (i.e., pregnancy‐related services, hospital bulletin boards) or online advertisements (19%), as part of a larger study on couples' relationships during the transition to parenthood (Fernandes et al, 2022; Tavares et al, 2021; Tavares, Rosen, et al, 2022, Tavares, Barros, et al, 2022; Tavares et al, 2023). Participants recruited through advertisements completed all materials online.…”
Section: Methodsmentioning
confidence: 99%